2007
DOI: 10.1007/s00438-007-0305-2
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate peroxidase gene family in tomato: its identification and characterization

Abstract: The antioxidative response, where ascorbate peroxidase (APX) is a key enzyme, is an integral part of the plant tolerance response to environmental stresses. As a first step towards the study of the physiological role and the regulation of the members of the Apx gene family, the orthologs of the stress-sensitive cultivated tomato Solanum lycopersicum cv. M82 (Slm) and of the wild salt-tolerant species S. pennellii acc. Atico (Spa) were identified by utilizing the tomato EST database, and characterized. A redund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 45 publications
(70 reference statements)
2
60
0
4
Order By: Relevance
“…The antioxidative systems also play an important role in protection against ROS under saline conditions (Mittova et al, 2004;Najami et al, 2008). In the present experiments, the activities of certain antioxidant enzymes, namely GR, catalase and APX, were significantly higher in salt-acclimated plants, contributing to the reduced degradation of chlorophyll molecules.…”
Section: Discussionsupporting
confidence: 45%
“…The antioxidative systems also play an important role in protection against ROS under saline conditions (Mittova et al, 2004;Najami et al, 2008). In the present experiments, the activities of certain antioxidant enzymes, namely GR, catalase and APX, were significantly higher in salt-acclimated plants, contributing to the reduced degradation of chlorophyll molecules.…”
Section: Discussionsupporting
confidence: 45%
“…CAT and APX are the important components of the antioxidant system, played a vital role in eliminating and maintaining the threshold level of H 2 O 2 in a range of cellular organelles (Najami et al 2008). Our results demonstrated that CAT and APX activities significantly induced at higher concentrations of elicitors which signify the production of ROS due to oxidative stress.…”
Section: Discussionmentioning
confidence: 53%
“…Recent genome-wide analysis in higher plants indicated that APX belongs to a multigenic family, since there are nine genes in Arabidopsis, eight in rice, and seven in tomato. [43][44][45] These APX families are further classified into three subfamilies according to subcellular localization, viz., chloroplastic, cytosolic, and microbody isoenzymes. 5) Chloroplastic isoenzymes have stroma-soluble (sAPX) and thylakoid membranebound (tAPX) forms.…”
Section: Enzymatic and Molecular Properties Of Apx Isoenzymesmentioning
confidence: 99%